Ionically conductive layer in an electrochromic device and method of making and use thereof
Patent Information
- Application Number
- CN202611102326.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-09-01
AI Technical Summary
目前广泛氧化硅、氧化钨、氧化镍、氧化硅铝薄膜作为离子传输层,但这些材料电子隔绝能力好的离子导通能力就偏差,离子导通能力好的,电子隔绝能力就偏差,无法实现两者兼顾
本发明通过对中间离子导通层薄膜的替换成高离子电导率及低电子电导率薄膜,有效提高离子电导率至3.0×10-8S/cm以上,优选条件下3.0×10-7S/cm以上,并实现对电子的较好隔绝,降低电子电导率至7.0×10-11S/cm以下,优选条件下8.5×10-12以下,避免有漏电流产生,从而提升器件的着褪色速度及降低着色稳定后的维持电压,电致变色器件的综合性能提升。
Smart Images

Figure CN122672247A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochromic electronic thin film assembly technology, and in particular to an ion-conducting layer in an electrochromic device, its preparation method, and its application. Background Technology
[0002] Electrochromic: Electrochromic is the phenomenon where the optical properties of a material (reflectivity, transmittance, absorptivity, etc.) undergo stable and reversible color changes under the influence of an applied electric field. Visually, this manifests as reversible changes in color and transparency. The ion-conducting layer is a thin film layer located between the anode and cathode layers, used to block electron transport but allowing lithium ions to pass through. Currently, with the increasingly widespread application of electrochromic products, industries such as automobiles, military, and construction can all utilize electrochromic technology. Vehicle rearview mirrors and sunroofs, military camouflage functions, and building windows can all use electrochromic technology for various purposes. Therefore, the fading speed and stability of the device after coloring are extremely important. Currently, silicon oxide, tungsten oxide, nickel oxide, and aluminum silicate thin films are widely used as ion transport layers. However, these materials have good electron isolation capabilities but poor ion conduction capabilities, and vice versa; it is impossible to achieve both simultaneously. The ion conduction layer in the middle of electrochromic devices has poor electron isolation performance. When voltage is applied to the electrodes on both sides, leakage current occurs, resulting in a slower fading speed and a higher stable voltage after coloring.
[0003] Therefore, providing a novel ion-conducting layer for electrochromic devices, its preparation method, and its application has become an urgent problem to be solved. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides an ion-conducting layer in an electrochromic device, its preparation method, and its application. By replacing the intermediate ion-conducting layer film with a film exhibiting high ion conductivity and low electronic conductivity, this invention achieves better isolation of electrons, avoids leakage current generation, thereby improving the fading speed of the device and reducing the holding voltage after color stabilization, thus enhancing the overall performance of the electrochromic device.
[0005] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides an ion conduction layer in an electrochromic device, wherein the electrochromic device is arranged in a stacked manner from bottom to top as follows: a glass substrate, a lower conductive electrode layer, an insulating layer, a cathode electrochromic layer, an ion conduction layer, an anode electrochromic layer, a lithium layer and an upper conductive electrode layer. The ion-conducting layer comprises a silicon oxynitride thin film.
[0006] This invention replaces the intermediate ion-conducting layer film with a silicon oxynitride film as the ion-conducting layer. Silicon oxynitride has a looser and more open amorphous network structure, which provides more and smoother migration channels for small ions such as lithium ions. This results in less resistance and faster movement of ions in the ion-conducting layer. In silicon oxynitride, the introduction of nitrogen atoms can effectively suppress the "tunneling effect" or "Purfrank effect". By increasing the difficulty of electron passage, leakage current is significantly reduced, giving it both high ion conduction capability and good electronic isolation capability. This improves the fading speed of the device and reduces the maintenance voltage after color stabilization, thus improving the overall performance of the electrochromic device.
[0007] As a preferred technical solution of the present invention, the thickness of the ion conduction layer is 25-100nm, for example, it can be 25nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0008] This invention achieves a better overall performance improvement for electrochromic devices by further limiting the thickness of the ion-conducting layer. When the thickness of the ion-conducting layer is too low, the electron blocking ability is insufficient, making it prone to leakage; when the thickness of the ion-conducting layer is too high, the ion transport path is too long, resulting in a slower response.
[0009] Preferably, the refractive index of the silicon oxynitride thin film is 1.6-1.7, for example, it can be 1.6, 1.61, 1.62, 1.63, 1.64, 1.65, 1.66, 1.67, 1.68, 1.69 or 1.7, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0010] In this invention, the refractive index of the silicon oxynitride thin film is further defined as 1.6-1.7, representing a high oxygen content and moderate nitrogen content in its composition. This composition endows the film with lower defect density, superior interface properties, and stronger electron blocking capability, which are its core advantages as a high-performance ion-conducting layer. A refractive index deviating from this range, whether too low or too high, will impair these key properties due to compositional imbalance.
[0011] In a second aspect, the present invention provides a method for preparing an ion-conducting layer in the electrochromic device described in the first aspect, wherein the ion-conducting layer is obtained by magnetron sputtering deposition on the cathode electrochromic layer.
[0012] As a preferred technical solution of the present invention, the power density of the magnetron sputtering is 5-10 kW / m, for example, it can be 5 kW / m, 6 kW / m, 7 kW / m, 8 kW / m, 9 kW / m or 10 kW / m, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0013] As a preferred technical solution of the present invention, the temperature of the magnetron sputtering coating is 30-100℃, for example, it can be 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃ or 100℃, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0014] The present invention further limits the temperature of magnetron sputtering coating during the preparation of the ion conduction layer. If the temperature of magnetron sputtering coating is too high, the coloring speed will be slowed down.
[0015] As a preferred technical solution of the present invention, the pressure of the magnetron sputtering coating is 0.2-4.0 Pa, for example, it can be 0.2 Pa, 0.5 Pa, 1.0 Pa, 2.0 Pa, 3.0 Pa or 4.0 Pa, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0016] As a preferred technical solution of the present invention, the gas in the magnetron sputtering includes argon, nitrogen and oxygen.
[0017] Preferably, the flow rate of argon gas in the magnetron sputtering gas is 100-500 sccm, for example, it can be 100 sccm, 200 sccm, 300 sccm, 400 sccm or 500 sccm, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0018] As a preferred technical solution of the present invention, the oxygen concentration in the magnetron sputtering gas is 20-60%, for example, it can be 20%, 30%, 40%, 50% or 60%, the nitrogen concentration is 20-60%, for example, it can be 20%, 30%, 40%, 50% or 60%, and the remainder is argon, but it is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0019] As a preferred technical solution of the present invention, the magnetron sputtering coating speed is 0.1-1.0 m / min, for example, it can be 0.1 m / min, 0.2 m / min, 0.3 m / min, 0.4 m / min, 0.5 m / min, 0.6 m / min, 0.7 m / min, 0.8 m / min, 0.9 m / min or 1.0 m / min, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0020] Thirdly, the present invention provides an electrochromic device as described in the first aspect, wherein the electrochromic device is applied in a smart window, a display device, or an anti-glare rearview mirror.
[0021] This invention improves the overall performance of the electrochromic film layer by replacing the intermediate ion-conducting layer, giving it both high ion conductivity and good electronic isolation capabilities. This makes the electrochromic film layer a promising candidate for application in smart windows, display devices, or anti-glare rearview mirrors.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects: This invention effectively improves the ionic conductivity to 3.0 × 10⁻⁶ by replacing the intermediate ion-conducting layer film with a film exhibiting high ionic conductivity and low electronic conductivity. -8 S / cm or higher, preferably 3.0×10⁻⁶ -7 With a conductivity of S / cm or higher, it achieves good electron isolation and reduces electronic conductivity to 7.0 × 10⁻⁶. -11 Below S / cm, preferably 8.5×10 -12 The following measures are taken to avoid leakage current, thereby improving the fading speed of the device and reducing the holding voltage after color stabilization, thus improving the overall performance of the electrochromic device. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of the electrochromic device provided by the present invention; Among them, 1-glass substrate; 2-lower conductive electrode layer; 3-insulating layer; 4-cathode electrochromic layer; 5-ion conducting layer; 6-anode electrochromic layer; 7-lithium layer; 8-upper conductive electrode layer. Detailed Implementation
[0024] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. However, the following examples are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.
[0025] Example 1 This embodiment provides an ion-conducting layer in an electrochromic device, the structure of which is as follows: Figure 1 As shown, the electrochromic device is arranged in layers from bottom to top as follows: a glass substrate, a lower conductive electrode layer, an insulating layer, a cathode electrochromic layer, an ion-conducting layer, an anode electrochromic layer, a lithium layer, and an upper conductive electrode layer; the ion-conducting layer is made of silicon oxynitride, the thickness of the ion-conducting layer is 50 nm, and the refractive index of the silicon oxynitride thin film is 1.65.
[0026] This embodiment also provides a method for preparing the ion-conducting layer in the electrochromic device. The ion-conducting layer is obtained by magnetron sputtering deposition on the cathode electrochromic layer. The power density of the magnetron sputtering is 8 kW / m, the temperature of the magnetron sputtering deposition is 60°C, the pressure of the magnetron sputtering deposition is 2 Pa, and the deposition speed is 0.5 m / min. The gas in the magnetron sputtering includes argon, nitrogen, and oxygen. The flow rate of argon in the magnetron sputtering gas is 300 sccm, and the oxygen concentration in the magnetron sputtering gas is 20%, the nitrogen concentration is 60%, and the remainder is argon.
[0027] Example 2 This embodiment provides an ion-conducting layer in an electrochromic device. The electrochromic device is arranged in layers from bottom to top: a glass substrate, a lower conductive electrode layer, an insulating layer, a cathode electrochromic layer, an ion-conducting layer, an anode electrochromic layer, a lithium layer, and an upper conductive electrode layer. The ion-conducting layer is made of silicon oxynitride, has a thickness of 25 nm, and has a refractive index of 1.6.
[0028] This embodiment also provides a method for preparing the ion-conducting layer in the electrochromic device. The ion-conducting layer is obtained by magnetron sputtering deposition on the cathode electrochromic layer. The power density of the magnetron sputtering is 5 kW / m, the temperature of the magnetron sputtering deposition is 30°C, the pressure of the magnetron sputtering deposition is 0.2 Pa, and the deposition speed is 1.0 m / min. The gas in the magnetron sputtering includes argon, nitrogen, and oxygen. The flow rate of argon in the magnetron sputtering gas is 100 sccm, and the oxygen concentration in the magnetron sputtering gas is 30%, the nitrogen concentration is 60%, and the remainder is argon.
[0029] Example 3 This embodiment provides an ion-conducting layer in an electrochromic device. The electrochromic device is arranged in layers from bottom to top: a glass substrate, a lower conductive electrode layer, an insulating layer, a cathode electrochromic layer, an ion-conducting layer, an anode electrochromic layer, a lithium layer, and an upper conductive electrode layer. The ion-conducting layer is made of silicon oxynitride, has a thickness of 100 nm, and has a refractive index of 1.7.
[0030] This embodiment also provides a method for preparing the ion-conducting layer in the electrochromic device. The ion-conducting layer is obtained by magnetron sputtering deposition on the cathode electrochromic layer. The power density of the magnetron sputtering is 10 kW / m, the temperature of the magnetron sputtering deposition is 100°C, the pressure of the magnetron sputtering deposition is 4.0 Pa, and the deposition speed is 0.1 m / min. The gas in the magnetron sputtering includes argon, nitrogen, and oxygen. The flow rate of argon in the magnetron sputtering gas is 500 sccm, and the oxygen concentration in the magnetron sputtering gas is 20%, the nitrogen concentration is 70%, and the remainder is argon.
[0031] Example 4 This embodiment provides an ion-conducting layer in an electrochromic device. The only difference from Embodiment 1 is that the thickness of the ion-conducting layer is adjusted from 50nm to 10nm, while the rest is the same as Embodiment 1.
[0032] Example 5 This embodiment provides an ion-conducting layer in an electrochromic device. The only difference from Embodiment 1 is that the thickness of the ion-conducting layer is adjusted from 50nm to 120nm, while the rest is the same as Embodiment 1.
[0033] Example 6 This embodiment provides an ion-conducting layer in an electrochromic device. The only difference from Embodiment 1 is that the magnetron sputtering temperature is 120°C when preparing the ion-conducting layer.
[0034] Example 7 This embodiment provides an ion-conducting layer in an electrochromic device. The only difference from Embodiment 1 is that, except for the refractive index of the silicon oxynitride thin film being 1.5, everything else is the same as in Embodiment 1.
[0035] Example 8 This embodiment provides an ion-conducting layer in an electrochromic device. The only difference from Embodiment 1 is that, except for the refractive index of the silicon oxynitride thin film being 1.8, everything else is the same as in Embodiment 1.
[0036] Comparative Example 1 This comparative example provides an ion-conducting layer in an electrochromic device. The only difference from Example 1 is that the ion-conducting layer is changed to silicon nitride, while the rest is the same as Example 1.
[0037] Comparative Example 2 This comparative example provides an ion-conducting layer in an electrochromic device. The only difference from Example 1 is that the ion-conducting layer is changed to zirconium oxide, while the rest is the same as Example 1.
[0038] Comparative Example 3 This comparative example provides an ion-conducting layer in an electrochromic device. The only difference from Example 1 is that the ion-conducting layer is changed to silicon oxide, while the rest is the same as Example 1.
[0039] Comparative Example 4 This comparative example provides an ion-conducting layer in an electrochromic device. The only difference from Example 1 is that the ion-conducting layer is changed to aluminum silicon oxide, while the rest is the same as Example 1.
[0040] Comparative Example 5 This comparative example provides an ion-conducting layer in an electrochromic device. The only difference from Example 1 is that, except that the ion-conducting layer is changed to tungsten oxide, everything else is the same as in Example 1.
[0041] Comparative Example 6 This comparative example provides an ion-conducting layer in an electrochromic device. The only difference from Example 1 is that the ion-conducting layer is changed to nickel oxide, while the rest is the same as Example 1.
[0042] Application Example 1 This application example provides an electrochromic device, which is arranged in layers from bottom to top as follows: a glass substrate, a lower conductive electrode layer, an insulating layer, a cathode electrochromic layer, an ion-conducting layer, an anode electrochromic layer, a lithium layer, and an upper conductive electrode layer; wherein, the ion-conducting layer adopts the ion-conducting layer of the electrochromic device provided in Example 1, the glass substrate has a thickness of 3 mm, the lower conductive electrode layer is an ITO thin film with a thickness of 500 nm, the insulating layer is a titanium oxide thin film with a thickness of 50 nm, the cathode electrochromic layer is a tungsten-niobium oxide thin film with a thickness of 300 nm, the anode electrochromic layer is a nickel oxide thin film with a thickness of 300 nm, the lithium film has a thickness of 100 nm, and the upper conductive electrode layer is an ITO thin film with a thickness of 500 nm.
[0043] This application example also provides a method for fabricating the electrochromic device, the method comprising: sequentially depositing a lower conductive electrode layer, an insulating layer, a cathode electrochromic layer, an ion-conducting layer, an anode electrochromic layer, a lithium layer, and an upper conductive electrode layer on a glass substrate using magnetron sputtering to obtain the electrochromic device; wherein, the ion-conducting layer is fabricated using the method provided in Example 1, and during the magnetron sputtering process of the lower conductive electrode layer, the deposition power density is 3 kW / m, the deposition temperature is 300 °C, and the deposition pressure is 0.5 Pa. The deposition rate was 0.5 m / min, the deposition gas was a mixture of argon and oxygen, the argon flow rate was 500 sccm, and the oxygen concentration was 0.3%; during the magnetron sputtering of the insulating layer, the deposition power density was 10 kW / m, the deposition temperature was 300℃, the deposition pressure was 0.5 Pa, the deposition rate was 0.5 m / min, the deposition gas was a mixture of argon and oxygen, the argon flow rate was 500 sccm, and the oxygen concentration was 50%; during the magnetron sputtering of the cathode electrochromic layer, the deposition power density was 1... The deposition parameters were: 5 kW / m, coating temperature 300℃, coating pressure 2 Pa, coating speed 0.5 m / min, and coating gas was a mixture of argon and oxygen with an argon flow rate of 500 sccm and an oxygen concentration of 70%. For the magnetron sputtering of the anodic electrochromic layer, the deposition power density was 15 kW / m, coating temperature 50℃, coating pressure 2 Pa, coating speed 0.5 m / min, and coating gas was a mixture of argon and oxygen with an argon flow rate of 300 sccm and an oxygen concentration of 80%. (Lithium layer) During the magnetron sputtering process, the coating power density is 5 kW / m, the coating temperature is 50 °C, the coating pressure is 0.5 Pa, the coating speed is 0.5 m / min, and the coating gas is argon with a flow rate of 500 sccm. During the magnetron sputtering process of the upper conductive electrode layer, the coating power density is 4 kW / m, the coating temperature is 100 °C, the coating pressure is 0.5 Pa, the coating speed is 0.5 m / min, and the coating gas is a mixture of argon and oxygen with a flow rate of 300 sccm and an oxygen concentration of 0.5%.
[0044] Application Example 2 This application example provides an electrochromic device, which is arranged in layers from bottom to top as follows: a glass substrate, a lower conductive electrode layer, an insulating layer, a cathode electrochromic layer, an ion-conducting layer, an anode electrochromic layer, a lithium layer, and an upper conductive electrode layer; wherein, the ion-conducting layer adopts the ion-conducting layer of the electrochromic device provided in Example 2, the thickness of the glass substrate is 0.4 mm, the lower conductive electrode layer is an ITO thin film with a thickness of 100 nm, the insulating layer is a titanium oxide thin film with a thickness of 25 nm, the cathode electrochromic layer is a tungsten niobium oxide thin film with a thickness of 500 nm, the anode electrochromic layer is a nickel oxide thin film with a thickness of 200 nm, the lithium film has a thickness of 50 nm, and the upper conductive electrode layer is an ITO thin film with a thickness of 200 nm.
[0045] This application example also provides a method for fabricating the electrochromic device, the method comprising: sequentially depositing a lower conductive electrode layer, an insulating layer, a cathode electrochromic layer, an ion-conducting layer, an anode electrochromic layer, a lithium layer, and an upper conductive electrode layer on a glass substrate by magnetron sputtering to obtain the electrochromic device; wherein, the ion-conducting layer is fabricated using the method provided in Example 2, and during the magnetron sputtering process of the lower conductive electrode layer, the deposition power density is 2 kW / m, the deposition temperature is 250 °C, and the deposition pressure is... The deposition pressure was 0.1 Pa, the deposition speed was 1.0 m / min, and the deposition gas was a mixture of argon and oxygen with an argon flow rate of 200 sccm and an oxygen concentration of 0.1%. During the magnetron sputtering of the insulating layer, the deposition power density was 5 kW / m², the deposition temperature was 250 °C, the deposition pressure was 0.3 Pa, the deposition speed was 0.1 m / min, and the deposition gas was a mixture of argon and oxygen with an argon flow rate of 50 sccm and an oxygen concentration of 30%. The magnetron sputtering of the cathode electrochromic layer... During the process, the coating power density was 10 kW / m², the coating temperature was 250℃, the coating pressure was 0.5 Pa, the coating speed was 0.1 m / min, and the coating gas was pure oxygen; during the magnetron sputtering of the anodic electrochromic layer, the coating power density was 10 kW / m², the coating temperature was 30℃, the coating pressure was 0.5 Pa, the coating speed was 0.1 m / min, and the coating gas was a mixture of argon and oxygen, with an argon flow rate of 100 sccm and an oxygen concentration of 60%; during the magnetron sputtering of the lithium layer... During the process, the coating power density was 2 kW / m, the coating temperature was 30℃, the coating pressure was 0.1 Pa, the coating speed was 0.1 m / min, and the coating gas was argon with a flow rate of 100 sccm. During the magnetron sputtering process of the upper conductive electrode layer, the coating power density was 2 kW / m, the coating temperature was 50℃, the coating pressure was 0.1 Pa, the coating speed was 0.1 m / min, and the coating gas was a mixture of argon and oxygen with a flow rate of 100 sccm and an oxygen concentration of 0.1%.
[0046] Application Example 3 This application example provides an electrochromic device, which is arranged in layers from bottom to top as follows: a glass substrate, a lower conductive electrode layer, an insulating layer, a cathode electrochromic layer, an ion-conducting layer, an anode electrochromic layer, a lithium layer, and an upper conductive electrode layer; wherein, the ion-conducting layer adopts the ion-conducting layer of the electrochromic device provided in Example 3, the glass substrate has a thickness of 5.0 mm, the lower conductive electrode layer is an ITO thin film with a thickness of 900 nm, the insulating layer is a titanium oxide thin film with a thickness of 100 nm, the cathode electrochromic layer is a tungsten niobium oxide thin film with a thickness of 200 nm, the anode electrochromic layer is a nickel oxide thin film with a thickness of 500 nm, the lithium film has a thickness of 150 nm, and the upper conductive electrode layer is an ITO thin film with a thickness of 900 nm.
[0047] This application example also provides a method for fabricating the electrochromic device, the method comprising: sequentially depositing a lower conductive electrode layer, an insulating layer, a cathode electrochromic layer, an ion-conducting layer, an anode electrochromic layer, a lithium layer, and an upper conductive electrode layer on a glass substrate by magnetron sputtering to obtain the electrochromic device; wherein, the ion-conducting layer is fabricated using the method provided in Example 3, and during the magnetron sputtering process of the lower conductive electrode layer, the deposition power density is 5 kW / m, the deposition temperature is 350 °C, the deposition pressure is 0.8 Pa, and the deposition... The deposition speed was 0.1 m / min, the coating gas was a mixture of argon and oxygen, the argon flow rate was 800 sccm, and the oxygen concentration was 0.6%; during the magnetron sputtering of the insulating layer, the deposition power density was 15 kW / m, the deposition temperature was 350℃, the deposition pressure was 0.8 Pa, the deposition speed was 1.0 m / min, and the coating gas was a mixture of argon and oxygen, the argon flow rate was 1000 sccm, and the oxygen concentration was 80%; during the magnetron sputtering of the cathode electrochromic layer, the deposition power density was 20 kW / m. The deposition parameters were: m, coating temperature 380℃, coating pressure 4.0Pa, coating speed 1.0m / min, and coating gas a mixture of argon and oxygen with an argon flow rate of 1000sccm and an oxygen concentration of 50%; For the magnetron sputtering of the anodic electrochromic layer, the deposition power density was 20kW / m, coating temperature 100℃, coating pressure 4.0Pa, coating speed 1.0m / min, and coating gas a mixture of argon and oxygen with an argon flow rate of 500sccm and an oxygen concentration of 80%; Lithium layer During the magnetron sputtering process, the coating power density was 10 kW / m, the coating temperature was 80 °C, the coating pressure was 1.0 Pa, the coating speed was 1.0 m / min, and the coating gas was argon with a flow rate of 1000 sccm. During the magnetron sputtering process of the upper conductive electrode layer, the coating power density was 6 kW / m, the coating temperature was 150 °C, the coating pressure was 1.0 Pa, the coating speed was 1.0 m / min, and the coating gas was a mixture of argon and oxygen with a flow rate of 500 sccm and an oxygen concentration of 1.0%.
[0048] Application Example 4 This application example provides an electrochromic device, which is the same as application example 1 except that the ion conduction layer is the same as the ion conduction layer in the electrochromic device provided in example 4.
[0049] Application Example 5 This application example provides an electrochromic device, which is the same as application example 1 except that the ion conduction layer is the same as the ion conduction layer in the electrochromic device provided in example 5.
[0050] Application Example 6 This application example provides an electrochromic device, which is the same as application example 1 except that the ion conduction layer is the same as the ion conduction layer in the electrochromic device provided in example 6.
[0051] Application Example 7 This application example provides an electrochromic device, which is the same as application example 1 except that the ion conduction layer is the same as the ion conduction layer in the electrochromic device provided in example 7.
[0052] Application Example 8 This application example provides an electrochromic device, which is the same as application example 1 except that the ion conduction layer is the same as the ion conduction layer in the electrochromic device provided in example 8.
[0053] Comparative Application Examples 1-6 This comparative application example provides an electrochromic device, which is the same as application example 1 except that the ion conduction layer is adopted from the ion conduction layer of the electrochromic devices provided in comparative examples 1-6.
[0054] Coloring tests were conducted on the electrochromic products prepared in corresponding use cases 1-8 and comparative application examples 1-6. Ionic conductivity and electronic conductivity were detected using a four-probe detector and electrochemical impedance spectroscopy. The transmittance of the electrochromic film and the time required for the lowest transmittance (coloring time) were detected using a spectrophotometer under the conditions of conditioning voltage of 1-5V and spectral range of 380-780nm.
[0055] The test results are shown in Table 1.
[0056] Table 1 The test results show that: (1) As can be seen from Application Examples 1 to 3, this invention, through optimization of the intermediate ion conduction layer material, uses silicon oxynitride thin film as the ion conduction layer, effectively improving the ion conductivity (reaching 3×10⁻⁶). -7 (S / cm or higher), reducing electronic conductivity (down to 8.5×10) -12 (S / cm below), coloring time is significantly shortened, and the overall performance of electrochromic devices is improved.
[0057] (2) As can be seen from the combined application examples 1 and 4 and 5, the present invention can achieve a better overall performance improvement of the electrochromic device by further limiting the thickness of the ion conduction layer. When the thickness of the ion conduction layer is too low, the electron blocking ability is insufficient and it is easy to "leak". When the thickness of the ion conduction layer is too high, the ion transport path is too long and the response is slow.
[0058] (3) As can be seen from the combined application examples 1 and 6, the present invention further limits the temperature of magnetron sputtering coating during the preparation of the ion conduction layer. When the temperature of magnetron sputtering coating is too high, the coloring speed will be slowed down.
[0059] (4) It can be seen from the combined application examples 1 and 7 and 8 that when the refractive index is low and the oxygen content is high, the ionic conductivity will decrease when the refractive index is high and the nitrogen content is high, resulting in a significant increase in coloring time.
[0060] (5) As can be seen from Example 1 and Comparative Examples 1-6, by optimizing the ion conduction layer material, the electrochromic device of the present invention has a higher ion conduction rate, which can improve the speed of lithium ion movement; at the same time, the low electron conductivity can effectively isolate electrons and reduce leakage problems; thus, it can both improve the movement of ions and hinder the movement of electrons, and the coloring speed is also accelerated, and the overall performance of the electrochromic device is significantly improved.
[0061] In summary, by optimizing the ion-conducting layer material, this invention uses silicon oxynitride thin film as the ion-conducting layer, which effectively improves ion conductivity, reduces electronic conductivity, significantly shortens coloring time, and enhances the overall performance of the electrochromic device.
[0062] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. An ion-conducting layer in an electrochromic device, characterized in that, The electrochromic device is arranged in layers from bottom to top as follows: glass substrate, lower conductive electrode layer, insulating layer, cathode electrochromic layer, ion conduction layer, anode electrochromic layer, lithium layer and upper conductive electrode layer. The ion-conducting layer comprises a silicon oxynitride thin film.
2. The ion-conducting layer according to claim 1, characterized in that, The thickness of the ion-conducting layer is 25-100 nm; Preferably, the refractive index of the silicon oxynitride thin film is 1.6-1.
7.
3. A method for preparing an ion-conducting layer in an electrochromic device according to claim 1 or 2, characterized in that, The ion-conducting layer is obtained by magnetron sputtering deposition on the cathode electrochromic layer.
4. The preparation method according to claim 3, characterized in that, The power density of the magnetron sputtering is 5-10 kW / m.
5. The preparation method according to claim 3 or 4, characterized in that, The temperature of the magnetron sputtering coating is 30-100℃.
6. The preparation method according to any one of claims 3-5, characterized in that, The pressure of the magnetron sputtering coating is 0.2-4.0 Pa.
7. The preparation method according to any one of claims 3-6, characterized in that, The gases used in the magnetron sputtering include argon, nitrogen, and oxygen; Preferably, the flow rate of argon gas in the magnetron sputtering gas is 100-500 sccm.
8. The preparation method according to any one of claims 3-7, characterized in that, The gas used in the magnetron sputtering has an oxygen concentration of 20-60%, a nitrogen concentration of 20-60%, and the remainder is argon.
9. The preparation method according to any one of claims 3-8, characterized in that, The magnetron sputtering deposition rate is 0.1-1.0 m / min.
10. An electrochromic device according to claim 1 or 2, characterized in that, The electrochromic device is used in smart windows, display devices, or anti-glare rearview mirrors.